Switching to Tenofovir Therapy Versus Continuation of Entecavir for Patients With Hepatitis B Virus Infection: A Systematic Review and Meta‐Analysis - Muhammad Shahzil; Ammad Javaid Chaudhary; Talha Kashif; Ali Akram Qureshi; Anza Muhammad; Faiza Khan; Muhammad Saad Faisal; Muhammad Ali Khaqan; Hassam Ali; Yara Dababneh; Dilip Moonka (JGH Open)
ABSTRACT Background Hepatitis B virus (HBV) infection causes liver disease, including hepatocellular carcinoma. Controlling viral activity is crucial to reducing complications. Tenofovir may offer benefits over entecavir, but it is unclear if switching from entecavir to tenofovir improves outcomes. This study assesses the clinical impact of switching to tenofovir therapy for chronic HBV infection. Methods Following the PRISMA guidelines, we conducted a literature search within the Cochrane Library, PubMed, MEDLINE, Embase, and Scopus for studies of patients with HBV infection who were switched to tenofovir from entecavir or were maintained on entecavir. Both formulations of tenofovir, that is, tenofovir disoproxil fumarate and tenofovir alafenamide were included and analyzed in subgroup analysis. Meta‐analyses were performed with RevMan 5.4 using a random‐effects model, with statistical significance set at p < 0.05. Results A total of eight studies, comprising 833 patients, were included in the meta‐analysis. Tenofovir showed a significantly higher likelihood of achieving complete virological response (RR 5.60; 95% CI 3.51–8.94; p < 0.00001) and a greater reduction in HBV DNA levels (MD −1.03 log IU/mL; 95% CI −1.69 to −0.36; p = 0.002) compared to entecavir. However, there was no significant difference in HBsAg reduction or HBeAg seroconversion between the two groups. ALT reductions were not statistically significant overall, although entecavir showed better outcomes in subgroup analysis. Conclusion Switching from entecavir to tenofovir improves virological response and reduces HBV DNA levels, but shows no significant advantage in HBsAg reduction, HBeAg seroconversion, or overall, ALT reduction.